Bifunctional MOF‐Derived Carbon Photonic Crystal Architectures for Advanced Zn–Air and Li–S Batteries: Highly Exposed Graphitic Nitrogen Matters. (26th July 2017) - Yang, Meijia; Hu, Xuanhe; Fang, Zhengsong; Sun, Lu; Yuan, Zhongke; Wang, Shuangyin; Hong, Wei; Chen, Xudong; Yu, Dingshan
Abstract : Nitrogen‐rich porous carbons (NPCs) are the leading cathode materials for next‐generation Zn–air and Li–S batteries. However, most existing NPC suffers from insufficient exposure and harnessing of nitrogen‐dopants (NDs), constraining the electrochemical performance. Herein, by combining silica templating with in situ texturing of metal–organic frameworks, a new bifunctional 3D nitrogen‐rich carbon photonic crystal architecture of simultaneously record‐high total pore volume (13.42 cm 3 g −1 ), ultralarge surface area (2546 m 2 g −1 ), and permeable hierarchical macro‐meso‐microporosity is designed, enabling sufficient exposure and accessibility of NDs. Thus, when used as cathode catalysts, the Zn–air battery delivers a fantastic capacity of 770 mAh gZn −1 at an unprecedentedly high rate of 120 mA cm −2, with an ultrahigh power density of 197 mW cm −2 . When hosting 78 wt% sulfur, the Li–S battery affords a high‐rate capacity of 967 mAh g −1 at 2 C, with superb stability over 1000 cycles at 0.5 C (0.054% decay rate per cycle), comparable to the best literature value. The results prove the dominant role of highly exposed graphitic‐N in boosting both cathode performances. Abstract : A new metal–organic‐framework‐derived N‐rich carbon photonic crystal architecture of simultaneously record‐high total pore volume (13.42 cm 3 g −1 ), superlarge surface area (2546 m 2 g −1 ), and permeable hierarchical macro‐meso‐microporosity is explored as bifunctional cathode materials for next‐generation Zn–air and Li–S batteries.